Innovation of Tuition Fee Payment through a Web-Based Information System Integrated with Digital Financial Services at SMK Mekanika Kota Bogor - Sinta Listari; Yayuk Nurjanah; Yanto Hermawan; Muhammad Aniq Hanif; Intan Vidya Mega Utami (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study addresses the challenges of manual tuition fee payment at SMK Mekanika Kota Bogor, including transaction delays, data inaccuracies, and limited transparency. It proposes a web-based payment information system integrated with digital financial services to streamline administrative processes. The study aims to design, implement, and evaluate a scalable digital solution that improves transaction speed, data accuracy, and stakeholder access to real-time payment information. Using a prototyping method and the Laravel framework, the system was developed with core modules for authentication, student and class data management, transaction processing, report generation, and payment history. Functionality was validated using black-box testing, achieving a 100% success rate across critical modules. Results indicate a reduction in average transaction time from 3–5 minutes to under one minute, along with a significant decrease in data entry errors and manual inquiries. User satisfaction reached a mean score of 4.3 on a 5-point scale. Although functional testing was successful, non-functional aspects such as performance under load and system security remain untested. The findings demonstrate the system’s technical reliability and offer a replicable model for digital payment innovation in vocational education. Keywords: Web-based payment system; digital finance integration; vocational school; process automation; transaction transparency.